THE UTILIZATION OF DRAGON FRUIT (HYLOCEREUS POLYRHIZUS) AND DIETARY COMBINATION TO PREVENT IRON DEFICIENCY ANAEMIA IN ADOLESCENCE GIRLS: LITERATURE REVIEW - Kinantika Nur Dewanti; Annisa Febriana (International Journal of Biomedical Nursing Review, 2025)
Introduction: Dragon fruit (Hylocereus polyrhizus) is a fruit rich in iron, which is beneficial for adolescenthealth, including preventing iron deficiency anemia. Dragon fruit can be consumed directly or combinedwith other foods. However, fruit and vegetable consumption among adolescents remains low. Even thoughdragon fruit is a fruit that is easy to reach and rich in iron. This may be due to a lack of awareness andinformation. Purpose: To determine the effect of dragon fruit and diet combination to prevent irondeficiency anemia in adolescent girls. Methods: The method used is a literature review of four databases,namely Google Scholar, Google, Science Direct and PubMed in the 2020-2025 period. Results: Based onthe 10 articles used in this literature review, it shows that dragon fruit and a combination of diets canincrease hemoglobin levels related to the prevention of iron deficiency anemia status in adolescentgirls.Conclusion: Dragon fruit and a combination of diets can be used as an alternative food to prevent irondeficiency anemia in adolescent girls.